THU0271 PERFORMANCE OF THE EULAR/ACR 2019 CLASSIFICATION CRITERIA FOR SYSTEMIC LUPUS ERYTHEMATOSUS IN EARLY DISEASE, ACROSS SEXES AND ETHNICITIES. (2nd June 2020) - Johnson, S.; Brinks, R.; Costenbader, K.; Daikh, D.; Mosca, M.; Ramsey-Goldman, R.; Smolen, J. S.; Wofsy, D.; Boumpas, D.; Kamen, D. L.; Jayne, D.; Cervera, R.; et al.
Abstract : Background: EULAR/ACR 2019 SLE Classification Criteria were validated in an international cohort. Objectives: To evaluate performance characteristics of SLE classification systems in sex, race/ethnicity, and disease duration subsets. Methods: Sensitivity and specificity of the EULAR/ACR 2019, SLICC 2012 and ACR 1982/1997 criteria were evaluated in the validation cohort. Results: The cohort consisted of female (n=1098), male (n=172), Asian (n=118), Black (n=68), Hispanic (n=124) and White (n=941) patients; and patients with an SLE duration of 1-3 years (n=196), 3-5 years (n=157), and ≥5 years (n=879). Among patients with 1-3 years disease duration, the EULAR/ACR criteria had better sensitivity than the ACR criteria (97% (95%CI 92-99%) vs 81% (95%CI 72-88%). The new criteria performed well in men (sensitivity 93%, specificity 96%) and women (sensitivity 97%, specificity 94%). The new criteria had better sensitivity than the ACR criteria in White (95% vs 83%), Hispanic (100% vs 86%) and Asian patients (97% vs 77%). Conclusion: The EULAR/ACR 2019 criteria perform well in patients with early disease, and across sexes and ethnicities. Disclosure of Interests: Sindhu Johnson Grant/research support from: Boehringer Ingelheim, Corbus Pharmaceuticals, GlaxoSmithKline, Roche, Merck, Bayer, Consultant of: Boehringer Ingelheim, Ikaria, Ralph Brinks: None declared, Karen Costenbader Grant/research support from: Merck, Consultant of: Astra-Zeneca, David Daikh: None declared, Marta Mosca: None declared, Rosalind Ramsey-Goldman: None declared, Josef S. Smolen Grant/research support from: AbbVie, Eli Lilly, Janssen, Merck Sharp & Dohme, Pfizer, Roche – grant/research support, Consultant of: AbbVie, Amgen Inc., AstraZeneca, Astro, Celgene Corporation, Celtrion, Eli Lilly, Glaxo, ILTOO, Janssen, Medimmune, Merck Sharp & Dohme, Novartis, Pfizer, Roche, Samsung, Sanofi, UCB – consultant, Speakers bureau: AbbVie, Amgen Inc., AstraZeneca, Astro, Celgene Corporation, Celtrion, Eli Lilly, Glaxo, ILTOO, Janssen, Medimmune, Merck Sharp & Dohme, Novartis, Pfizer, Roche, Samsung, Sanofi, UCB – speaker, David Wofsy: None declared, Dimitrios Boumpas Grant/research support from: Unrestricted grant support from various pharmaceutical companies, Diane L Kamen Consultant of: Consulted on SLE survey development for Lilly and consulted on SLE trial protocol development for EMD Serono in 2019, David Jayne Grant/research support from: ChemoCentryx, GSK, Roche/Genentech, Sanofi-Genzyme, Consultant of: Astra-Zeneca, ChemoCentryx, GSK, InflaRx, Takeda, Insmed, Chugai, Boehringer-Ingelheim, Ricard Cervera: None declared, Nathalie Costedoat-Chalumeau Grant/research support from: UCB to my institution, Betty Diamond: None declared, Dafna D Gladman Grant/research support from: AbbVie, Amgen Inc., BMS, Celgene Corporation, Janssen, Novartis, Pfizer, UCB – grant/research support, Consultant of: AbbVie, Amgen Inc., BMS, Celgene Corporation, Janssen, Novartis, Pfizer, UCB – consultant, Bevra H. Hahn Grant/research support from: Janssen Research & Development, LLC, Falk Hiepe: None declared, Soren Jacobsen: None declared, Dinesh Khanna Shareholder of: Eicos Sciences, Inc./Civi Biopharma, Inc., Grant/research support from: Dr Khanna was supported by NIH/NIAMS K24AR063120, Consultant of: Acceleron, Actelion, Bayer, Boehringer Ingelheim, Bristol-Myers Squibb, Corbus Pharmaceuticals, Horizon Therapeutic, Galapagos, Roche/Genentech, GlaxoSmithKline, Mitsubishi Tanabe, Sanofi-Aventis/Genzyme, UCB, Kirsten Lerstrom: None declared, Elena Massarotti: None declared, William Joseph McCune: None declared, Guillermo Ruiz-Irastorza: None declared, Jorge Sanchez-Guerrero: None declared, Matthias Schneider: None declared, Murray B Urowitz: None declared, George Bertsias Grant/research support from: GSK, Consultant of: Novartis, Bimba F. Hoyer: None declared, Nicolai Leuchten: None declared, Chiara Tani: None declared, Sara Tedeschi: None declared, Zahi Touma: None declared, Gabriela Schmajuk Grant/research support from: Pfizer, Branimir Anic: None declared, Florence Assan: None declared, Tak Chan: None declared, Ann E Clarke: None declared, Mary K. Crow: None declared, László Czirják Consultant of: Actelion, BI, Roche-Genentech, Lilly, Medac, Novartis, Pfizer, Bayer AG, Andrea Doria Consultant of: GSK, Pfizer, Abbvie, Novartis, Ely Lilly, Speakers bureau: UCB pharma, GSK, Pfizer, Janssen, Abbvie, Novartis, Ely Lilly, BMS, Winfried Graninger: None declared, Bernadett Halda-Kiss: None declared, Sarfaraz Hasni: None declared, Peter Izmirly: None declared, Michelle Jung: None declared, Gabor Kumanovics Consultant of: Boehringer, Teva, Speakers bureau: Roche, Lilly, Novartis, Xavier Mariette: None declared, Ivan Padjen: None declared, Jose M Pego-Reigosa: None declared, Juanita Romero-Diaz Consultant of: Biogen, Iñigo Rua-Figueroa: None declared, Raphaèle Seror Consultant of: BMS, Medimmune, Novartis, Pfizer, GSK, Lilly, Georg Stummvoll: None declared, Yoshiya Tanaka Grant/research support from: Asahi-kasei, Astellas, Mitsubishi-Tanabe, Chugai, Takeda, Sanofi, Bristol-Myers, UCB, Daiichi-Sankyo, Eisai, Pfizer, and Ono, Consultant of: Abbvie, Astellas, Bristol-Myers Squibb, Eli Lilly, Pfizer, Speakers bureau: Daiichi-Sankyo, Astellas, Chugai, Eli Lilly, Pfizer, AbbVie, YL Biologics, Bristol-Myers, Takeda, Mitsubishi-Tanabe, Novartis, Eisai, Janssen, Sanofi, UCB, and Teijin, Maria Tektonidou Grant/research support from: AbbVie, MSD, Novartis and Pfizer, Consultant of: AbbVie, MSD, Novartis and Pfizer, Carlos Vasconcelos: None declared, Edward Vital Grant/research support from: AstraZeneca, Roche/Genentech, and Sandoz, Consultant of: AstraZeneca, GSK, Roche/Genentech, and Sandoz, Speakers bureau: Becton Dickinson and GSK, Daniel J Wallace: None declared, Sule Yavuz: None declared, Pier Luigi Meroni: None declared, Marvin Fritzler: None declared, Raymond Naden: None declared, Thomas Dörner Grant/research support from: Janssen, Novartis, Roche, UCB, Consultant of: Abbvie, Celgene, Eli Lilly, Roche, Janssen, EMD, Speakers bureau: Eli Lilly, Roche, Samsung, Janssen, Martin Aringer Consultant of: Boehringer Ingelheim, Roche, Speakers bureau: Boehringer Ingelheim, Roche